PENGARUH PENERAPAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA DEALER AUTO 2000 SUTOYO MALANG - Zulmi, Reyza (Jurnal Ilmiah Mahasiswa FEB, 2016)
Motivation is the processes that account for an individual's intensity, direction, and persistence of effort toward attaining a goal. Motivation consist of two kinds aspect namely external and internal. External motivation is motivation comes from outside theirselves employee like fee, job condition and insurance. Internal motivation is motivation comes from inside theirselves employee like job comfortable, interesting and challanging. Perfomance is an result of employeeâ€™s perfomance to measure of the ratio between output and input that can be achieved within a certain time. This study aim to know, describe and analyze in application of job motivation and will be effect perfomance employees. Job motivation referred external and internal motivation in AUTO 2000 Malang-Sutoyo. In this study, the researcher used a type of quantitative research with descriptive approach and used percentage method and regression. The researcher used sample is 82 employees. Collecting data used questionnare and documantation. Based on the result the research got in regression Y = 4.470 + 0.130 X1 + 0.778 X2 using SPSS 16 statistic. The result of hypothesis F test showed F hit = 307.253 with siginifican = 0,000 < 0,05 it mean H3 with sounds â€œThere is influenced significan between external and internal on perfomance employeesâ€ received. Whereas from hypoyhesis test partial (t test) got t hit from variable external motivation that is equal 10.468 where probabilities lower that 0,05 so hypothesis is received. Koefisien determinasi (Adjusted R2) equal 0,883, its mean that 88,3% perfomance influenced by external and internal.Key Word : Motivation, Perfomance